2018
DOI: 10.1016/j.coph.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel therapeutic targets for diabetes through improved understanding of islet adhesion receptors

Abstract: Adhesion receptors are transmembrane proteins that mediate cell-cell and cell-matrix communications. In addition to their adhesive role in maintaining islet architecture, they are also important for promoting islet cell survival, proliferation and secretory function. Their capacity for improving β-cell mass and insulin secretion suggest that they may be suitable targets for pharmacological intervention, and their interactions with extracellular matrix proteins hold promise in improving islet transplantation ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Dried and crushed T. grandis leaves were immersed in cold 75% ethanol for 12 h and then extracted at room temperature. The aforementioned procedures were repeated three times, and the extracted solutions were combined and concentrated by a vacuum thin-film concentration device at 60°C [ 22 ]. The concentrated solution was dispersed by ultrasound in an appropriate amount of water and then extracted successively with petroleum ether, ethyl acetate, and n-butanol.…”
Section: Methodsmentioning
confidence: 99%
“…Dried and crushed T. grandis leaves were immersed in cold 75% ethanol for 12 h and then extracted at room temperature. The aforementioned procedures were repeated three times, and the extracted solutions were combined and concentrated by a vacuum thin-film concentration device at 60°C [ 22 ]. The concentrated solution was dispersed by ultrasound in an appropriate amount of water and then extracted successively with petroleum ether, ethyl acetate, and n-butanol.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding other ECMs, integrins α1β1, α2β1, α3β1, α6β1, α7β1, and α6β4 are the receptors for laminin [77], and integrins α3β1, α4β1, α5β1, α8β1, α9β1, αvβ1, αIIbβ3, αvβ3, αvβ6, and α4β7 are receptors for fibronectin [78,79]. On the other hand, it has been shown that islets harbor at least five integrin heterodimers, including α1β1, α3β1, α5β1, αvβ1, and α6β1 [80]. In other words, islets can attach to white adipose tissue via a combination of collagen, laminin, fibronectin, and integrin, which may contribute to the engraftment of islets to white adipose tissue.…”
Section: Ecm Of White Adipose Tissuementioning
confidence: 99%
“…studied (Olaniru and Persaud, 2018). Efforts to translate integrin--cell-ECM interactions to T2D therapies have made little progress due to the sheer complexity of integrin/ECM interactions and non-specificity of ligand binding.…”
Section: The Extracellular Matrix and -Cell Functionmentioning
confidence: 99%